2016
DOI: 10.22159/ajpcr.2016.v9i6.14177
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Memory and Acetylcholinesterase Activity by Michelia Champaca in Chronically Noise Stressed Wistar Albino Rats

Abstract: Objective: The ability of an organism to adapt to aversive stressful situations or life challenging circumstances is very crucial to its state of health and survival. However, the breakdown in adaptation due to persistent uncontrollable stress leads to impairment of bodily functions and the onset of a variety of pathological disorders, especially memory decline. This study was designed to evaluate the effect of Michelia champaca a potent antioxidant on chronic noise-stress-induced memory impairment in rats.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(24 reference statements)
0
0
0
Order By: Relevance
“…There are numerous processes that take place in between a stressful input and the body's ensuing reactions. Both the central and autonomic nervous systems are involved in a range of neurochemical reactions throughout these activities (36) . The result of the present research showed that noise exposure for four hours per day for 15 days at increasing intensities of 85 dB, 100 dB and 135 dB caused significant reduction in the levels of serum dopamine and serotonin in contrast to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous processes that take place in between a stressful input and the body's ensuing reactions. Both the central and autonomic nervous systems are involved in a range of neurochemical reactions throughout these activities (36) . The result of the present research showed that noise exposure for four hours per day for 15 days at increasing intensities of 85 dB, 100 dB and 135 dB caused significant reduction in the levels of serum dopamine and serotonin in contrast to the control group.…”
Section: Discussionmentioning
confidence: 99%